Pengaruh Pemberian Kompos Campuran Ampas Tebu dan Kotoran Ayam terhadap Kesuburan Ultisol dan Hasil Produksi Kedelai (Glycine max (L.) merril) - Fuadi, Najla Anwar; Dewanti, Ayu (Universitas Batanghari Jambi, 2024)
Ultisol is a soil that contains low nutrients N, P and K and has the potential for Al-poisoning. Ultisol also has a low Cation Exchange Capacity, acidic soil pH and is sensitive to erosion. Improvements need to be made to increase Ultisol productivity, one of which is by adding organic ingredients. In addition to sugarcane bagasse compost, chicken manure contains many benefits because it contains a lot of organic materials that are good for the soil and plants. Increasing soybean yield is one of the priorities and can be done by utilizing Ultisol land. The purpose of this study is to determine the effect of composting a mixture of bagasse and chicken manure on ultisol fertility and soybean crop production. The research method carried out is experimental by conducting initial analysis of soil samples, compost application, maintenance, harvesting, soil analysis after compost application, calculation of height and crop yield. The results obtained were that the application of mixed compost of bagasse and chicken manure did not have a real effect on soil pH, P-available and Aldd, but could increase soil pH and P-available and lower Aldd in the soil. The application of mixed compost of bagasse and chicken manure was significantly different from plant height and was very different for soybean yield with the highest crop P3 (average plant height of 84.678 cm) and the highest yield of P3 3.938 tons/ha. The recommended treatment for soybean plants is P3 treatment with a dose of 15 tons/ha.